Evidence-based treatment of hip and pelvic injuries in runners - Geraci, M. C.; Brown, W. (Physical Medicine & Rehabilitation Clinics of North America, 2005)
The runner is especially at risk for development of injury to the hip and pelvis secondary to chronic repetitive microtrauma. The key to treatment is establishing complete and accurate diagnosis, and, in particular, identifying the functional biomechanical deficits in the kinetic chain that contribute to this repetitive microtrauma. A long-term successful outcome and prevention of reinjury are more likely if the focus of rehabilitation is on the restoration of the functional kinetic chain, rather than on a specific injured tissue. For example, the typical treatment of "iliotibial band syndrome" is a stretching protocol that frequently is unsuccessful in the long-term improvement of symptoms. A functional biomechanical approach might identify that the injured runner has lack of calcaneal eversion and a structurally rigid supinated foot. These functional biomechanical deficits would lead to inadequate internal rotation of the tibia and femur and result in inhibition or decreased recruitment of the gluteal muscles, in particular the gluteus medius. Restoring pronation throughout the lower extremity would require joint play techniques or functional joint mobilizations for the foot and ankle. In addition, a running shoe with a cushioned heel may be necessary to promote pronation and to attenuate shock. Exercises that integrate foot and hip function, including balance reaches, lunges and step-downs, are prescribed to stimulate the gluteus medius and other gluteals in positions that simulate running. Activities that are done in this manner activate the entire functional kinetic chain of muscles and joints. The nonoperative sports medicine specialist, in particular the physiatrist and physical therapist, are in an excellent position to integrate treatment of the entire functional kinetic chain through a thorough biomechanical evaluation and comprehensive rehabilitation of the injured runner. Additional training in the areas of biomechanical evaluation and functional biomechanical deficits should be sought, because residency and even many fellowship-trained programs often overlook these important areas. Finally, the injured runner is best taken care of in a setting in which different sports medicine specialists are available and work well as a team. No one sports medicine specialist can provide all of the needs to the injured runner.